RADIOGRAPHIC ASSESSMENT OF PERFORATION REPAIR QUALITY- AN OBSERVATIONAL STUDY - Jose, Jerry; S, Deepak.; Sugumaran, Surendar (International Journal of Psychosocial Rehabilitation, 2020)
Perforation of a tooth is an unfortunate event caused in the endodontic practice that can be induced by various factors such as iatrogenic resorption or by caries. The prognosis of these scenarios depends on various factors like the site of perforation and seal quality. The aim of the current study is to do an observational analysis using electronic medical records from the time frame of April 2019 to April 2020 in which all the cases of perforation repair were assessed. The site of perforation and the seal quality were assessed radiographically, and a score was given depending on the level of quality. From the results achieved, crown perforation and furcal perforation were seen to be observed most. The chi-square test was used to assess the association statistics and was shown to be statistically insignificant (p > 0.005), thus showing there is no correlation between site of perforation and quality of seal. The sealing of the perforation site was done usually with bioaggregate material -MTA—and the seal quality was judged to be overall satisfactory in the crown region, with the furcal region being least satisfactory.